THE EFFECT OF TEACHERS PEDAGOGIC COMPETENCY ON THE LEARNING OUTCOMES OF STUDENTS - Sudargini, Yuli; PURWANTO, AGUS (Journal of Industrial Engineering & Management Research, 2020)
This study aims to determine the effect of pedagogic competence on student learning outcomes. The population in this study were 41 students of physics class at high school in Pati. Collecting data by observation, interviews and distributing questionnaires. The questionnaire method was used to collect data on the independent variables of Pedagogic Competence and the dependent variable on Learning Outcomes. Test the research instrument by testing the validity and reliability test. The data analysis technique used is multiple regression analysis, coefficient of determination, t test and F test with a significance level of 0.05. Before analyzing the data, the analysis prerequisite test was conducted, including the normality test, multicollinearity test and heteroscedasticity test. The results of this study indicate that there is a significant influence between pedagogical competence on student learning outcomes in the learning evaluation course.